Increasing Critical Thinking Skills Through the Development of STEM-Based Physics Learning Media on Temperature and Heat - Aris Doyan; Ayu Safitri Melita; Muh Makhrus (Postgraduate, University of Mataram, 2023)
Research has been carried out to improve students' critical thinking skills which are valid, practical, and effective through the development of STEM-based learning media products on temperature and heat material. Data collection techniques used response questionnaires, validation sheets and test instruments, with the 4D model (Design, Define, Development, and Desiminate) as the design. Evaluation of product validity was carried out by media experts and material experts and used Aiken-V as a way of analysis. The practicality of the product is analyzed using a practicality test while the effectiveness is obtained by increasing students' mastery of concepts and critical thinking skills with N-gain. The results of the validator's assessment of the digital calorimeter media showed an average result of Aiken-V of 0.94 which was very valid. The average results for the practicality assessment of the developed media can be seen from the student response questionnaire which shows a value of 4.51 in the fairly practical category. The average result for the effectiveness of the developed media can be seen from the increase in critical thinking skills, namely 0.42 with moderate criteria. It was concluded that STEM-based physics learning media to improve students' critical thinking skills are valid, practical, and effective